(The effect cooking time and sugar addition on the quality of traditional food "Akam" - Indra Neffi Ridwan; Tatang Gumelar; Ella T.S; Hasnelly - (Warta Industri Hasil Pertanian, 1995)
The research is aimed at studying the effect of cooking time and sugar addition on the quality of traditional food "akam".The cooking time used are 25,30 and 30 minutes.Addition of cane sugar for the portion of 25,30 and 35 to the dough for the material of "akam".The result showed that the best product are obtained from 25 minutes cooking time and 30 portion addition of cane sugar.The chemical compositions is as follows: moisture content 6.88%, total sugar 35.70% ash 1.05% and peroxide value 0.76 mg oxygen/100 g sample